Türkiye'de dolarizasyon sorunu ve bankaların karlılığa dayalı performanslarına etkileri - TUNAY, KAŞİF BATU; TUNAY, NECLA (My University, 2022)
In economies with high inflationary pressures and strong dollarization, banks' FX liabilities are taken into account as one of the criteria for dollarization. It is believed that bank-based dollarization can have significant effects on bank performance. In this study, the effects of increasing foreign currency liabilities, especially foreign currency deposits, on the performance of the banking system in Turkey were analyzed empirically. Dynamic panel data estimations were made using the 2002-2020 period data of 27 banks with different ownership structures operating in the Turkish banking system. Findings show that dollarization positively affects bank performance, although it is not obvious. It has not been determined that dollarization has any effect on the operational profitability of banks. On the other hand, dollarization reduces the average cost of resources and increases the capital profitability of banks. However, this positive effect is valid for the periods when exchange rates are stable. If the exchange rate destabilizes, for example, significant exchange rate shocks occur, the dollarization will increase the cost of capital of banks and cause serious losses.

Yüksek enflasyonist baskılar yaşanan ve dolarizasyonun güçlü olduğu ekonomilerde, bankaların yabancı para yükümlülükleri dolarizasyonun ölçütlerinden biri olarak dikkate alınmaktadır. Banka temelli dolarizasyonun, banka performansına önemli etkileri olabileceğine inanılmaktadır. Bu çalışmada, Türkiye’de başta döviz mevduatları olmak üzere artan yabancı para yükümlülüklerinin banka sisteminin performansına olan etkileri deneysel olarak analiz edilmiştir. Türk banka sisteminde faaliyet gösteren farklı mülkiyet yapısındaki 27 bankanın 2002-2020 dönemi verileri kullanılarak dinamik panel veri tahminleri yapılmıştır. Ulaşılan bulgular, belirgin olmasa da dolarizasyonun banka performansını pozitif şekilde etkilediğini göstermektedir. Dolarizasyonun bankaların operasyonel karlılıkları üzerinde herhangi bir etkisi olduğu saptanamamıştır. Buna karşılık dolarizasyon ortalama kaynak maliyetini indirgeyerek bankaların sermaye karlılıklarını yükseltmektedir. Ancak bu olumlu etki kurların istikrarlı seyrettiği dönemler için geçerlidir. Kur istikrarı bozulursa, örneğin önemli kur şokları yaşanırsa, dolarizasyon bankaların kaynak maliyetlerini arttıracak ve ciddi zararlara neden olacaktır.
Dollarization problem in turkey and its effects on banks' profitability based performance
Keywords: Dolarizasyon; Banka Performansı; Karlılık; Sistem GMY Tahmincisi; Dollarization; Bank Performance; Profitability; System GMM Estimator